2016
DOI: 10.1038/mp.2016.90
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem evidence of cerebral inflammation in schizophrenia: a systematic review

Abstract: Schizophrenia is a psychiatric disorder which has a lifetime prevalence of ~1%. Multiple candidate mechanisms have been proposed in the pathogenesis of schizophrenia. One such mechanism is the involvement of neuroinflammation. Clinical studies, including neuroimaging, peripheral biomarkers and randomized control trials, have suggested the presence of neuroinflammation in schizophrenia. Many studies have also measured markers of neuroinflammation in postmortem brain samples from schizophrenia patients. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
215
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(243 citation statements)
references
References 172 publications
(269 reference statements)
9
215
1
4
Order By: Relevance
“…Therefore, increases in numbers or activity of these cells in schizophrenia have been hypothesized (48,49). In postmortem studies, higher levels of brain glial cell markers, such as human leukocyte antigenantigen D related and CD11b, have been observed in patients, although results have been mixed (50)(51)(52). With regard to astrocyte markers, there is no evidence of any overall FC, frontal cortex; H0, null hypothesis; H1, hypothesis 1; H2, hypothesis 2; H0:H1, BF denoting evidence in favor of H0 over H1; H1:H0, BF denoting evidence in favor of H1 over H0; H0:H2, BF denoting evidence in favor of H0 over H2; H2:H0, BF denoting evidence in favor of H2 over H0; H1:H2, BF denoting evidence in favor of H1 over H2; H2:H1, BF denoting evidence in favor of H2 over H1; HIP, hippocampus; M1, Model 1; TC, temporal cortex; TSPO, translocator protein; V T , total distribution volume.…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increases in numbers or activity of these cells in schizophrenia have been hypothesized (48,49). In postmortem studies, higher levels of brain glial cell markers, such as human leukocyte antigenantigen D related and CD11b, have been observed in patients, although results have been mixed (50)(51)(52). With regard to astrocyte markers, there is no evidence of any overall FC, frontal cortex; H0, null hypothesis; H1, hypothesis 1; H2, hypothesis 2; H0:H1, BF denoting evidence in favor of H0 over H1; H1:H0, BF denoting evidence in favor of H1 over H0; H0:H2, BF denoting evidence in favor of H0 over H2; H2:H0, BF denoting evidence in favor of H2 over H0; H1:H2, BF denoting evidence in favor of H1 over H2; H2:H1, BF denoting evidence in favor of H2 over H1; HIP, hippocampus; M1, Model 1; TC, temporal cortex; TSPO, translocator protein; V T , total distribution volume.…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%
“…Meta-analysis of TSPO in Patients With Psychosis differences between patients and control subjects (51,52). In the case of TSPO, which is expressed in microglia and astrocytes among other cells (8,9,53), autoradiographic studies have reported both higher (28) and lower (54) binding in patients as compared with HCs.…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%
“…SERPINA3 has been involved in the pathology of a number of devastating human diseases including Parkinson’s disease and Alzheimer’s disease. The disease can arise from gene expression disturbances that result in excess uncontrolled target protease activity and disruption of the downstream pathway [6, 10, 11]. It was reported that Nur77 (NR4A1) regulate SERPINA3 expression in astrocytes and HepG2 human liver cancer cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple lines of evidence from immunohistochemical cell counting studies to clinical trials of a non-selective microglial inhibitor support the fact that microglia is involved in the pathophysiology of SCZ [181]. Nevertheless, as with post mortem studies [182], microglia PET studies provided conflicting results. Indeed, some studies revealed significantly higher TSPO radioligand binding in SCZ patients in total gray matter [171,175], especially in the frontal and temporal lobes [175] and the hippocampus [172] than in controls subjects.…”
Section: Clinical Input Of Tspo Pet Imaging In Neurodegenerative Dmentioning
confidence: 99%